2013
DOI: 10.1021/es4023738
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Metabolism of a Novel Cis-Nitromethylene Neonicotinoid Paichongding in Aerobic Soils

Abstract: Many pesticides are chiral but used as racemic mixtures, even though their stereoisomers are often degraded stereoselectively in soils. Evaluation of degradation of chiral compounds is mostly focused on the enantioselectivity rather than diastereoselectivity/epimer preferences. In this study, we explored the diastereoselective transformation of paichongding (IPP), a novel chiral neonicotinoid with broad-spectrum insecticidal activity, to several degradation intermediates in different soils. (14)C-Labeling coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…The same amount of nitrogen-purged deionized water was added to compensate for evaporated loss of water. At 0, 5,11,20,31,45,60,76, and 100 days after the treatment, the flow-through vacuum desiccators were flushed for 30 min with a continuous nitrogen stream (99.99% pure). Soils without 14 C-stereoisomers were incubated as controls.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same amount of nitrogen-purged deionized water was added to compensate for evaporated loss of water. At 0, 5,11,20,31,45,60,76, and 100 days after the treatment, the flow-through vacuum desiccators were flushed for 30 min with a continuous nitrogen stream (99.99% pure). Soils without 14 C-stereoisomers were incubated as controls.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Interestingly, the activities against alfalfa aphids of the four stereoisomers of paichongding differed significantly, with (5R,7S)-> (5S,7S)-≥ (5S,7R)-> (5R,7R)paichongding. 20 Li et al reported that mineralization, extractable residues, and bound residue formation of paichongding were diastereoselective. 21 Wang et al found that after foliar application, no stereoselective absorption was observed among the enantiomers of paichongding, whereas significant stereoselective translocation in plants was observed between its epimers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], a dataset of 302 compounds with known pesticide activity was selected and used further for a 3D-similarity search. The conformational space of selected compounds was carried out with the Omega tool, Openeye (OMEGA v.2.5.1.4, OpenEye Scientific Software, Santa Fe, NM, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were conducted using the methods of Fu et al (2013). Before spiking with 14 C‐BKM, the soils were incubated in the dark for 15 d, and their water‐holding capacity was adjusted to 40% using distilled water to revive microbial activity.…”
Section: Methodsmentioning
confidence: 99%
“…Treated soil samples were transferred to 500‐mL Erlenmeyer flasks that were subsequently attached to a flow‐through apparatus with a series of airtight flasks containing absorbent solutions, as described by Fu et al (2013). The trap solutions were refreshed periodically throughout the incubation period.…”
Section: Methodsmentioning
confidence: 99%